2017
DOI: 10.1080/00207454.2017.1398158
|View full text |Cite
|
Sign up to set email alerts
|

Association of VDR gene polymorphisms with risk of relapsing-remitting multiple sclerosis in an Iranian Kurdish population

Abstract: As a result, Fok-I and Taq-I showed significant association with risk of MS, while Apa-I and Bsm-I were not observed to be related to the risk of the disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The first study to report a relationship between MS and BsmI polymorphism was based on the Japanese population, it showed that the TT genotype as well as the T allele were significantly higher in MS group compared to the control group (OR= 2.38, p= 0.0263 and OR= 2.45, p= 0.0138, respectively). 35 However, a study on Canadian population found no association between BsmI polymorphisms on the VDR gene and MS. 36 The findings of the present study are consistent with those reported by other studies done by Abdollahzadeh et al, 2017, 37 Africa, where Egypt is located, revealed no association between the BsmI mutation and MS. 38 . In addition, the study of Zheng et al, 2018 17 did not find any association between BsmI polymorphisms and MS susceptibility in the overall populations, Asians, and Caucasians.…”
Section: Discussionsupporting
confidence: 93%
“…The first study to report a relationship between MS and BsmI polymorphism was based on the Japanese population, it showed that the TT genotype as well as the T allele were significantly higher in MS group compared to the control group (OR= 2.38, p= 0.0263 and OR= 2.45, p= 0.0138, respectively). 35 However, a study on Canadian population found no association between BsmI polymorphisms on the VDR gene and MS. 36 The findings of the present study are consistent with those reported by other studies done by Abdollahzadeh et al, 2017, 37 Africa, where Egypt is located, revealed no association between the BsmI mutation and MS. 38 . In addition, the study of Zheng et al, 2018 17 did not find any association between BsmI polymorphisms and MS susceptibility in the overall populations, Asians, and Caucasians.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic variations in the VDR gene such as single nucleotide polymorphisms (SNPs) might influence the activity, stability, and expression levels of VDR products (mRNAs and/or proteins), subsequently altering the VD-VDR signaling axis, ultimately leading to disturbance of VD immune-regulatory functions. To date, a vast amount of investigations have been accomplished regarding the association of VDR polymorphisms with susceptibility to different diseases, including autoimmune disorders, cancers, viral and bacterial respiratory infections ( Valdivielso and Fernandez, 2006 ; Laplana et al, 2018 ; Abdollahzadeh et al, 2016 ; Abdollahzadeh et al, 2018 ). Collectively, a few VDR gene variants that have been observed in relation to predisposing to various conditions with contradictory results include Apa I (rs7975232; intron 8; C > A), Bsm I (rs1544410; intron 8; G > A), Tru9I (rs757343; intron 8; G > A), TaqI (rs731236; exon 9; A > G), Bgl I (rs739837; 3′UTR region; C > T), Fok I (rs2228570; exon 2; C > T), CDX2 (rs11568820; promoter; G > A), and Eco RV or A-1012G/GATA (rs4516035; promoter; T > C).…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that same allele could be corresponded to lower vitamin D 55‐57 . In both studies of Turkish 58 and Kurdish 59 cohorts, the statistical incidence of FokI between case and control groups was different. When the vitamin D was taken daily, it significantly reduced the risk of MS among those carrying GG genotype 60,61 .…”
Section: Discussionmentioning
confidence: 91%